Internalisasi Ajaran Tri Hita Karana Untuk Anak Usia Dini Pada Masa Pandemi Covid 19: Tri Hita Karana Untuk Anak Usia Dini Pada Masa Pandemi Covid 19 - Dwi Harianti (Kamaya: Jurnal Ilmu Agama, 2021)
Covid 19 had reached 2.832.755 cases which made the government gave some policies, one of them is online learning. Online learning should be hold in every educational level such as in Early Childhood Education. Early Childhood Education is the initial foundation for children to form good character. In order to form children character, educate them about the harmony between human and God (parahyangan), between human and human (pawongan) and between human and the universe (palemahan) are really important. Considering the short focus of students, it will be challenging for teachers, parents and students to do the online learning. This attracted the author's attention to conduct a study with the aim of knowing the process of internalizing Tri Hita Karana concept for early childhood during the covid 19 pandemic. This research was conducted using a descriptive qualitative method. The results of study indicate that the process of internalizing Tri Hita Karana concept still can be implemented during the COVID-19 pandemic through an online learning. Which learning is associated with the reality of children's daily lives through various activities and a consistent habituation process based on the lesson schedule. Teamwork between teacher and parent are really important to do this online learning in order to reach the learning goals.